Preservation strategies of lemon (Citrus aurantifolia): effects of temperature and storage on fruit quality - Cedeño , Fanny; Celi, Adriana; Intriago , Frank; Zambrano , Freddy; Mieles, Dayana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Lemon (Citrus aurantifolia Swingle) is an economically and nutritionally important crop whose shelf life is limited by rapid postharvest deterioration. Losses occurring during storage affect key quality attributes such as firmness, moisture retention, and juice content, making it necessary to identify effective conservation strategies. The objective of this study was to evaluate the effect of different storage temperatures and durations on the postharvest quality of lemon fruits produced in Manabí, Ecuador. A randomized block design with a 4 × 3 factorial arrangement was used, including four temperatures (10, 12, 14, and 26 °C) and three storage periods (9, 12, and 15 days), with four replications and a total of 800 fruits per locality. Physical and chemical characteristics such as fruit weight, diameter, juice content, pericarp weight, pH, and total soluble solids were evaluated. The results showed that storage at 12 °C and 14 °C better preserved fruit quality, whereas storage at 10 °C accelerated dehydration and increased pericarp weight loss. It is concluded that storage temperature is a determining factor in maintaining the postharvest quality of lemon fruits, and this study provides essential information to optimize handling practices and reduce losses along the production chain.